Διερεύνηση του ρόλου της αντίληψης του αιθυλενίου στους μηχανισμούς άμυνας τομάτας κατά του μύκητα Fusarium oxysporum f. sp. lycopersici. - Παπαγεωργίου, Στέλλα (Department of Agricultural Sciences, Biotechnology and Food Sciences, Cyprus University of Technology, 2013)
Fusarium oxysporum is a soil-born fungal pathogen that causes vascular browning, leaf epinasty, progressive wilting and plant death in a wide range of economically important crops. The control of F. oxysporum is especially difficult because the fungus survives for several years in the soil as resting structures, chlamydospores. In this study, mutant tomato lines Never ripe (Nr) and wilt type (WT) plants were used to determine the role of ethylene’s perception via Nr receptor in the plants response to infection by the soil-borne pathogen Fusarium oxysporum f. sp. lycopersici. Pathogenicity experiments showed that Fusarium oxysporum f. sp. lycopersici caused typical wilting symptoms in tomato plants but there was a statistically significant increase in disease severity of Nr compared to the wilt type plants. Fungal quantification experiments were performed using Real-time PCR in Nr and WT plants after inoculation with the pathogen in order to study whether the disease severity is associated with the fungal biomass within the vascular tissues of the plants. The results of fungal quantification revealed that the increase in symptom severity in the Nr mutant plants was associated with greater fungal growth in the vascular tissues of the Nr plants compared to the wild-type plants. The data from the pathogencity experiments and fungal quantification indicated that the Nr plants showed reduced resistance to the fungus. In order to study whether the defense mechanisms of Nr plants were compromised, the expression level of several defense related genes involved in the salicylic acid (SA), jasmonic acid (JA) and ethylene (ET) transduction pathways was tested with Real-time PCR. The transcript levels of all examined genes (PR1, PR2a, PR2b, PR5, CHI3, CHI4, CHI5) were calculated in both genotypes in response to Fusarium oxysporum f.sp. lycopersici 4 days post inoculation. The transcript levels of the SA-depended defense genes PR1, PR2a and PR5 were significantly higher in WT compared to Nr plants. The results of this study suggest that the inability of ET perception via Nr receptor in tomato plants leads to the suppression of the SA-dependent defense mechanisms; thus the plants become more susceptible to fungal infection with Fusarium oxysporum f. sp. lycopersici.
Keywords: Fusarium oxysporum; Τomato; Ethylene